Neurosensory Rehabilitation and Olfactory Network Recovery in Covid-19-related Olfactory Dysfunction - Chung, Tom Wai-Hin (Brain Sci, 2021)
Non-conductive olfactory dysfunction (OD) is an important extra-pulmonary manifestation of coronavirus disease 2019 (COVID-19). Olfactory bulb (OB) volume loss and olfactory network functional connectivity (FC) defects were identified in two patients suffering from prolonged COVID-19-related OD. One patient received olfactory treatment (OT) by the combination of oral vitamin A and smell training via the novel electronic portable aromatic rehabilitation (EPAR) diffusers. After four-weeks of OT, clinical recuperation of smell was correlated with interval increase of bilateral OB volumes [right: 22.5 mm(3) to 49.5 mm(3) (120%), left: 37.5 mm(3) to 42 mm(3) (12%)] and improvement of mean olfactory FC [0.09 to 0.15 (66.6%)].